Effect of the Problem-solving on the Mental Well-being of Mothers With Autistic Children - Keivan Kakabaraee; Maryam Seidy (Gonabad University of Medical Sciences, 2021)
Background: The birth of an exceptional child in a family can decrease the mental well-being of family members. This study aimed to investigate the effect of the family-centered problem-solving intervention on the mental well-being of the mothers of children with autism spectrum disorder. Methods: This was a quasi-experimental research with a pre-test, post-test, follow-up design and a control group. The statistical population of the study included all the mothers of children with autism disorder in Kermanshah City. Using the purposeful sampling method, we selected 30 mothers of autistic children studying at a rehabilitation center and randomly assigned them into the two groups of experimental (n=15) and control (n=15). In this study, the Satisfaction With Life Scale (Diener et al., 1985) and the Positive and Negative Affect Schedule (Watson et al., 1988) were used to measure mental well-being. After collecting the pre-test data of the mothers in the experimental group, 10 2-hour sessions (for a month) of family-centered problem-solving programs were administered. Also, the post-test and follow-up phases were executed after the end of the sessions and a 1-month interval, respectively. Finally, the obtained data were analyzed considering the repeated measures design. Results: The results showed a significant difference between the pre-test and post-test scores in the variable studied. However, the post-test and follow-up scores did not significantly differ in the variable studied. Conclusion: The results of this study supported the effectiveness of family-centered problem-solving training intervention on mental well-being and its subscales. Therefore, the family-centered problem-solving training program is of great importance as a preventive program.